Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan Joglo Girli Resto & Café Kulon Progo, Yogyakarta - Dwi Astuti; Kristiana Sri Utami (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this study was to determine the effect of motivation and work discipline on employee productivity at Joglo Girli Resto & Café in Kulon Progo, Yogyakarta. The company's access to high-quality human resources (HR) is very important. There is even an assumption that having access to good human resources is essential to achieving success. Therefore, to achieve high quality human resources, the organization as a whole must participate as much as possible in the process of developing its own human resources (HR investment). Regression, correlation, and hypothesis testing were used in statistical analysis in this study. The results of this study, employee productivity is significantly influenced by motivation by 14.6%. After hypothesis testing, the t value > t table, or (2.185 > 2.048). Employee productivity is significantly influenced by work discipline by 48.8%. After testing the hypothesis, the value of t count> t table (5.165> 2.101). Employee productivity is significantly influenced by work discipline and motivation simultaneously, as seen in the regression equation Y = 0.749 + 0.110 X1 + 0.665 X2. The contribution of influence is 45.8%, and the hypothesis test results in F count greater than F table, or (13.231 > 2.947).